Analisis Stabilitas Lereng Disposal Pada Desain In Pit Dump E, Daerah Lawang Kidul, Kabupaten Muara Enim, Sumatra Selatan - Prasetiawati, Septika; Dava, M. Hajjrol; Radityo, Daniel (PROGRAM STUDI TEKNIK GEOLOGI FAKULTAS TEKNOLOGI MINERAL UPN VETERAN YOGYAKARTA, 2025)
Open pit mining for coal requires an effective approach to overburden management, frequently employing in pit dumping (spoil disposal in excavated pits). However, water ponding and mud accumulation at the pit floor are critical variables that increase the potential for slope instability and the risk of landslides. This research aims to quantitatively analyze the stability of the proposed in pit dump design slopes at PT Pamapersada Nusantara, Muara Enim, South Sumatra, focusing on the impact of maximum mud conditions. The stability analysis was conducted using the Limit Equilibrium Method (LEM), specifically the Morgenstern-Price method, applied across six cross-sections. Four sections (A–D) represent the initial design, and two sections (E–F) represent the maximum mud conditions. The calculated Factor of Safety (FS) revealed significant contrasts. Based on the standard set by the Minister of Energy and Mineral Resources Decree No. 1827 K/30/MEM Year 2018 (FS > 1.3), only sections C–C’ (FS = 2.304) and D–D’ (F = 2.271) are classified as safe. Conversely, the four remaining sections (A–A’, B–B’, E–E’, and F–F’) have FS values below the critical threshold of 1.3. Specifically, sections E–E’and F–F’ showed very low FS values, confirming that the presence of mud is the dominant factor causing instability. This indicates that most of the dump slopes are at high risk of failure and categorized as unsafe. Consequently, these analysis results provide a critical foundation for consideration in the planning of future slope geometry redesigns